Perceptual compensation for differences in speaking style - Vitela, A. Davi; Warner, Natasha; Lotto, Andrew J. (Frontiers in Psychology, 2013)
It is well-established that listeners will shift their categorization of a target vowel as a function of acoustic characteristics of a preceding carrier phrase. These results have been interpreted as an example of perceptual normalization for variability resulting from differences in talker anatomy. The present study examined whether listeners would normalize for acoustic variability resulting from differences in speaking style within a single talker. Two vowel series were synthesized that varied between central and peripheral vowels (the vowels in “beat”‐“bit” and “bod”‐“bud”). Each member of the series was appended to one of four carrier phrases that were spoken in either a “clear” or “reduced” speech style. Participants categorized vowels in these eight contexts. A reliable shift in categorization as a function of speaking style was obtained for three of four phrase sets. This demonstrates that phrase context effects can be obtained with a single talker. However, the directions of the obtained shifts are not reliably predicted on the basis of the speaking style of the talker. Instead, it appears that the effect is determined by an interaction of the average spectrum of the phrase with the target vowel.